2023
DOI: 10.3390/ijms24108980
|View full text |Cite
|
Sign up to set email alerts
|

The Role of REV-ERB Receptors in Cancer Pathogenesis

Abstract: REV-ERB receptors are members of the nuclear receptor superfamily of proteins, which act as both intracellular receptors and transcription factors, therefore modulating the expression of target genes. REV-ERBs act as transcription repressors because of their unique structure. Their predominant role involves the control of peripheral circadian rhythmicity by participating in a transcription–translation feedback loop with other major clock genes. Regarding their role in cancer pathogenesis, recent studies in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The crude was purified by flash column chromatography (SiO 2 ), eluting with CH 2 Cl 2 /MeOH from 100 to 96:4 to afford 18 as yellow oil (0.049 g, 11% over 4 steps). UPLC/MS (method B): (19). Compound 19 was prepared according to the general procedure N using aldehyde 40l (0.032 g, 0.13 mmol), amine 30e (0.023 g, 0.13 mmol), and NaBH(OAc) 3 (0.054 g, 0.26 mmol) in anhydrous CH 2 Cl 2 (1.30 mL).…”
Section: Synthesis Of Rac-1-(4-fluorophenyl)-n-[[3-[[122-trimethyl-4p...mentioning
confidence: 99%
See 1 more Smart Citation
“…The crude was purified by flash column chromatography (SiO 2 ), eluting with CH 2 Cl 2 /MeOH from 100 to 96:4 to afford 18 as yellow oil (0.049 g, 11% over 4 steps). UPLC/MS (method B): (19). Compound 19 was prepared according to the general procedure N using aldehyde 40l (0.032 g, 0.13 mmol), amine 30e (0.023 g, 0.13 mmol), and NaBH(OAc) 3 (0.054 g, 0.26 mmol) in anhydrous CH 2 Cl 2 (1.30 mL).…”
Section: Synthesis Of Rac-1-(4-fluorophenyl)-n-[[3-[[122-trimethyl-4p...mentioning
confidence: 99%
“…An additional strategy to overcome the limitations deriving from the need of high doses of CQ and HCQ for inhibiting tumor growth is represented by a multitarget approach targeting both autophagy and pathways associated with autophagy-dependent cancer cell death. We previously reported that REV-ERB, a nuclear receptor regulating circadian rhythm and metabolism, plays a role in sustaining cancer cell survival when the autophagy flux is compromised . Indeed, pharmacological inhibition of REV-ERB significantly enhanced the cytotoxic activity of CQ against breast cancer cells, and cells from different cancer types knocked-down for REV-ERB were more sensitive to CQ-induced cell death. , In addition, the knockdown of the essential autophagy gene ATG5 in breast cancer cells enhanced the toxicity of the REV-ERB antagonist, SR8278 (Figure ), further indicating that REV-ERB inhibition induces cell death when autophagy is inhibited …”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to experimentally discover small molecules modulating the REV-ERB activity 8 . The small molecules discovered have been pharmacologically used to regulate the REV-ERB activity in several disease models such as Alzheimer’s, Duchenne Muscular Dystrophy (DMD), type-2 diabetes mellitus (T2DM), obesity, HIV replication cycle, non-alcoholic fatty liver disease (NAFLD), and cancer 917 . While most studies have reported the role of small molecules on α isoform, only a few studies have looked at the β isoform 8, 18, 19 .…”
Section: Introductionmentioning
confidence: 99%